STRATEGI PEMBERDAYAAN UMKM JATIM DALAM MENGHADAPI MASA PANDEMI - Diana Rapitasari; Soehardi Soehardi (Jurnal Ilmiah Manajemen Ubhara, 2021)
Following the COVID-19 pandemic, Micro, Small, and Medium Enterprises (MSMEs) play a critical role in supporting national economic growth. The MSME sector has been particularly hard hit by the COVID-19 pandemic, which has disrupted supply and demand as well as supply chains, causing the economy's wheels to grind to a halt at the MSME level. MSMEs must be supported by the government and other stakeholders in order to grow and develop. The goal of empowering MSMEs is to achieve a balanced, developing, and equitable national economic structure, as well as to boost regional development, job creation, income distribution, economic growth, and poverty alleviation. The East Java Provincial Government has developed a policy as a strategy for empowering MSMEs in East Java, so that MSMEs are not disrupted in their development process during the pandemic.Keywords : strategy, MSME empowerment, pandemic